Online Formative Assessments in English Teaching and Learning - Muhammad Shofri Firdaus; Entika Fani Prastikawati; Wiyaka Wiyaka (STAIN Sultan Abdurrahman Kepulauan Riau, 2022)
Some changes occur in the assessment process in the English teaching and learning process during the pandemic Covid-19. The integration of technology in the assessment process becomes a crucial need for the English teachers to run the online or blended English teaching. For that reason, this present study presents the the current implementation of online formative assessment in private and public junior high school in Semarang and the challenges that the English teachers face during the implementation. In this study, the writers carried out descriptive qualitative research design in which it used observation and an interview as the instruments. Two English teachers were involved in this study. The findings show that the implementation of online formative assessment runs well in both private and public junior high school. It is proved by the use of some online formative assessment tools during English teaching and learning such as Quizizz, Google Form, Socrative, Kahoot!, and Microsoft Teams routinely. On the other hand, during the implementation of online formative assessment, the English teachers also face some problems; students’ academic dishonesty and teachers’ poor computer skills. Finally, it is suggested that the English teachers need to improve their computer and digital literacy for supporting the implementation of online formative assessments during the online and blended English teaching.